Enfermarse y curarse en la guajira: la salud entre tradición y modernidad - Rincón Soto, Lucía (2007)
From the perspective of anthropology of medicine –which describes, analyzes and interprets the medical dimension of social groups, especially the origin, cure and prevention of illness–, this paper analyzes the Wayúu conception of the people they turn to in order to find a cure to their illnesses; the Wayúu Indians (Arawak) live on both sides of the Colombian-Venezuelan border. Due to the contact with the mestizo culture, in general, and in their search for cure their illnesses in particular, the Wayúu have adjusted many of their healing practices; they have abandoned some of them and have adopted alien ones. As a result they now find themselves in permanent conflict between their traditions and the alternatives offered by the Western biomedical model.